Therapeutic hypothermia is associated with improved neurologic outcome and survival in cardiac arrest survivors of non-shockable rhythms - Lundbye, Justin B.; Rai, Mridula; Ramu, Bhavadharini; Hosseini-Khalili, Alireza; Li, Dadong; Slim, Hanna B.; Bhavnani, Sanjeev P.; Nair, Sanjeev U.; Kluger, Jeffrey (Resuscitation, 2012)
Therapeutic hypothermia improves neurologic outcomes in patients resuscitated from cardiac arrest due to ventricular fibrillation. However, its role in patients with cardiac arrest due to non-shockable rhythms (pulseless electrical activity (PEA) and asystole) is unclear. We hypothesized that therapeutic hypothermia favorably impacts neurologic outcome and survival in patients resuscitated from cardiac arrest due to non-shockable rhythms. Retrospectively collected data on consecutive adult patients admitted to Hartford Hospital from 1/1/2004 to 11/1/2010 who survived a cardiac arrest due to PEA or asystole were analyzed. Patients who underwent therapeutic hypothermia (1/1/2007–11/1/2010) formed the hypothermia group while patients admitted prior to the institution of therapeutic hypothermia (1/1/2004–1/1/2007) at Hartford Hospital formed the control group. The primary end-point was measured using the Pittsburgh cerebral performance category (CPC) scale and patients were assessed for a good (CPC 1 and 2) or poor (CPC 3–5) neurological outcome prior to discharge from hospital. A secondary end-point was measured as survival at discharge from hospital. Of 100 post-cardiac arrest patients included in the study, 15/52 (29%) patients in the hypothermia group had a good neurologic outcome as compared to 5/43 (10%) patients in the control group (P=0.021). On multivariate analysis, the odds ratio for good neurologic outcome and survival at discharge from the hospital with therapeutic hypothermia as compared to control were 4.35 (95% CI 1.10–17.24, P=0.04) and 5.65 (CI 1.66–19.23, P=0.006) respectively. Therapeutic hypothermia is associated with favorable neurologic outcome and survival in patients resuscitated after cardiac arrest due to non-shockable rhythms.